Functional polymorphisms of FAS and FASL gene and risk of breast cancer - pilot study of 134 cases. - Mohammad Hashemi (Public Library of Science (PLoS), 2013)
Fas/Fas ligand (FasL) system is one of the key apoptotic signaling entities in the extrinsic apoptotic pathway. De-regulation of this pathway, i.e. by mutations may prevent the immune system from the removal of newly-formed tumor cells, and thus lead to tumor formation. The present study investigated the association between -1377 G/A (rs2234767) and -670 A/G (rs1800682) polymorphisms in Fas as well as single nucleotide polymorphisms INV2nt -124 A/G (rs5030772) and -844 C/T (rs763110) in FasL in a sample of Iranian patients with breast cancer. This case-control study was done on 134 breast cancer patients and 152 normal women. Genomic DNA was extracted from whole blood samples. The polymorphisms were determined by using tetra-ARMS-PCR method. There was no significant difference in the genotype distribution of FAS rs2234767 polymorphism between cases and controls. FAS rs1800682, FASL rs5030772, and FASL rs763110 genotypes showed significant associations with an increasing risk of breast cancer (odds ratio OR = 3.18, P = 0.019; OR = 5.08, P = 0.012; OR = 2.40, P = 0.024, respectively). In conclusion, FAS rs2234767 was not associated with breast cancer risk. Though, FAS rs1800682, FASL rs5030772, and FASL rs763110 polymorphisms were associated with the risk of breast cancer in the examined population.